(3JaSjQ GdbQBfs - (3GdMSf Hf eMeO Hf MHjH Hf CjhH CHh GdbGSe GdfjSGHhQj,J (B406 (3g` s
(3ChdgG (B:s
(3jHJOF HChd ShQI GdeDefhf s
(3BNQgG (B:s
(3hjfJgi HBNQ GdbQBf s
(3LRA efgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B213s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B29 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B460s
(3eUOQ GbJfGA GdCUd (B:s
(3ajV Gddg (B(50) s
Keywords: (3GdJaSjQ hYdhe GdbQBfs